Retrospective evaluation of 140 dogs involved in road traffic accidents. (17th February 2018) - Klainbart, Sigal; Bibring, Uri; Strich, Dalia; Chai, Orit; Bdolah‐Abram, Tali; Aroch, Itamar; Kelmer, Efrat
Abstract : This study has retrospectively reviewed the medical records of 140 dogs sustaining road traffic accident (RTA), and has examined the population characteristics, medical history, injury type, physical examination, emergency laboratory tests and radiography findings, the animal trauma triage (ATT) score, the length of hospitalisation, the complications and the outcome. The survival rate was 83.2 per cent. Younger dogs sustained more frequently lung contusions and limb fractures, while larger dogs more frequently suffered limb fractures, and smaller dogs and older ones sustained more frequently pelvic fractures and sacroiliac luxation (P<0.05 for all). Dogs sustaining orthopaedic injuries required longer hospitalisation (P<0.001). The survival rates of non‐ambulatory dogs (P<0.001) and those with neurological abnormalities (P<0.001), abnormal body temperature (P=0.001), hyperglycaemia (P=0.026) or hypoproteinaemia (P=0.04) at presentation were lower compared with those in which these were absent. The number of injured body systems was significantly (P<0.001) and positively associated with death. Dogs surviving RTA to presentation to the hospital have a good prognosis for survival to discharge. Older age, and high ATT score, abnormal body temperature, neurological deficits, hyperglycaemia and hypoproteinaemia at presentation, and occurrence of multiorgan trauma are negative prognostic indicators in such dogs.